Does the emotional design of scaffolds enhance learning and motivational outcomes in game‐based learning?. (30th August 2022) - Koskinen, Antti; McMullen, Jake; Ninaus, Manuel; Kiili, Kristian
Abstract: Background: In recent years, the importance of emotions in learning has been increasingly recognized. Applying emotional design to induce positive emotions has been considered a means to enhance the instructional effectiveness of digital learning environments. However, only a few studies have examined the specific effects of emotional design in game‐based learning. Objectives: This quasi‐experimental study utilized a value‐added research approach to investigate whether emotional design applied to scaffolding in a game‐based learning environment improves learning and motivational outcomes more than emotionally neutral scaffolding. Methods: A total of 138 participants, mean age of 11.5 ( SD  = 0.73) participated in the study. A total of 68 participants played the base version of a fraction learning game (Number Trace), where scaffolding was provided with emotionally neutral mathematical notations, and 70 participants played the value‐added version of the game using emotionally designed animated scaffolding agents. Pre‐and post‐tests were used to measure conceptual fraction knowledge and self‐reported measures of situational interest and situational self‐efficacy to evaluate motivational outcomes. Results and Conclusions: Our results indicate that the emotional design applied to scaffolds can improve the educational value of a game‐based learning environment by enhancing players' situational interest and situational self‐efficacy. However, although the intervention improved the participants' conceptual fraction knowledge, there was no significant difference between the scaffolding conditions in participants' learning outcomes. Takeaways: The results suggest that emotional design can increase the educational impact of game‐based learning by promoting the development of interest, as well as improving self‐efficacy. Lay Description: What is currently known about the subject matter: Learning games that include scaffolding can enhance learning outcomes. Emotional design can enhance learning outcomes. Only a few studies have examined effects of emotional design in game‐based learning. There are no studies examining the effects of emotional design of scaffolding. What this paper adds to this: The study is the first to examine the effects of emotionally designed scaffolds in game‐based learning. Emotional design applied to scaffolds did not enhance learning more than emotionally neutral scaffolds. Emotional design applied to scaffolds enhanced participants' situational interest and situational self‐efficacy. The implications of study findings for practitioners: The study confirms that math games that include number line mechanics and scaffolding can be effective. The results demonstrated that emotional design of scaffolds did not harm learning. The results confirm that emotional design of instructional features is useful as it can enhance motivational outcomes. Learning effects of emotionally designed features should be examined with longer interventions.